Presence of SARS-CoV-2 transcripts in the choroid plexus of MS and non-MS patients with COVID-19 - Fuchs, Vidmante; Kutza, Michael; Wischnewski, Sven; Deigendesch, Nikolaus; Lutz, Luc; Kulsvehagen, Laila; Ricken, Gerda; Kappos, Ludwig; Tzankov, Alexandar; Hametner, Simon; Frank, Stephan; Schirmer, Lucas; et al. (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2021)
Although primarily targeting the respiratory system, coronavirus disease 2019 (COVID-19) affects the CNS in up to 80% of patients.[1][1] Yet, findings on COVID-19 neuropathology have been conflicting: autopsy reports range from inflammatory CNS syndromes, cerebrovascular events,[1][1] and
Gesehen am 18.08.2021